Antifibrotic and Anti-Inflammatory Actions of α-Melanocytic Hormone: New Roles for an Old Player - Roshan Dinparastisaleh; Mehdi Mirsaeidi (MDPI AG, 2021)
The melanocortin system encompasses melanocortin peptides, five receptors, and two endogenous antagonists. Besides pigmentary effects generated by α-Melanocytic Hormone (α-MSH), new physiologic roles in sexual activity, exocrine secretion, energy homeostasis, as well as immunomodulatory actions, exerted by melanocortins, have been described recently. Among the most common and burdensome consequences of chronic inflammation is the development of fibrosis. Depending on the regenerative capacity of the affected tissue and the quality of the inflammatory response, the outcome is not always perfect, with the development of some fibrosis. Despite the heterogeneous etiology and clinical presentations, fibrosis in many pathological states follows the same path of activation or migration of fibroblasts, and the differentiation of fibroblasts to myofibroblasts, which produce collagen and α-SMA in fibrosing tissue. The melanocortin agonists might have favorable effects on the trajectories leading from tissue injury to inflammation, from inflammation to fibrosis, and from fibrosis to organ dysfunction. In this review we briefly summarized the data on structure, receptor signaling, and anti-inflammatory and anti-fibrotic properties of α-MSH and proposed that α-MSH analogues might be promising future therapeutic candidates for inflammatory and fibrotic diseases, regarding their favorable safety profile.